2012
DOI: 10.1016/j.jcrs.2012.02.040
|View full text |Cite
|
Sign up to set email alerts
|

Effect of lubricating eyedrops on ocular light scattering as a measure of vision quality in patients with dry eye

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 16 publications
(14 reference statements)
4
32
0
4
Order By: Relevance
“…Diaz-Valle et al [16] reported that no significant differences were found in intraocular scattering over a 20-second period, which was consistent with our findings. To our knowledge, this is the first published study to assess the detailed optical quality parameters using the double-pass method, such as the MTF cutoff frequency and the Strehl ratio, which are considered to have a large impact on visual performance.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Diaz-Valle et al [16] reported that no significant differences were found in intraocular scattering over a 20-second period, which was consistent with our findings. To our knowledge, this is the first published study to assess the detailed optical quality parameters using the double-pass method, such as the MTF cutoff frequency and the Strehl ratio, which are considered to have a large impact on visual performance.…”
Section: Discussionsupporting
confidence: 93%
“…Our results are in line with those reported in dry eye patients by Diaz-Valle et al [16] It is suggested that an unstable tear film may play a role in enhancing ocular scattering in eyes with short TBUT, and that these change rates are potential indicators for differentiating short-TBUT eyes from normal eyes. A more detailed analysis should be performed to determine the exact role of the change rate of optical quality in eyes with short TBUT.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…[31][32][33][34][35][36][37][38][39][40][41][42] Moreover, the double-pass system is capable of monitoring postblink dynamic changes in optical quality associated with changes in the tear film. [43][44][45][46][47] Previous investigations using sequential HOA measurements showed that postblink dynamic changes in optical quality occur even in clinically normal subjects and revealed that such postblink changes in dry eyes can be classified into two patterns. 33,38,39 In dry eyes with a decreased tear film break-up time and dry eye symptoms without ocular surface damage and tear deficiency, the HOA pattern exhibited an upward curve after blinking that continued to increase.…”
Section: Accommodationmentioning
confidence: 99%